Melon Cultivation Guidance for Empowering Women in Pajagan Village, Sumedang Regency - Rahmat Budiarto; Wawan Sutari; Farida; Mochamad Arief Soleh; Anne Nuraini; Syariful Mubarok; Kusumiyati; Siska Rasiska; Noor Istifadah; Luciana Djaya (Research and Social Study Institute, 2025)
Background: As one of popular fruit, melon is potentially to cultivate in homeyard by housewives.Aims: This community service is carried out in July 2025, for empowering women in Pajagan Village, Cisitu District, Sumedang Regency through melon cultivation guidance.Method: Thirty-five participants joined, mostly local women housewives aged 25–50 from the PKK organization, along with 15 students aged 20–22 conducting fieldwork. This work documents the initial stages of home melon cultivation through a participatory approach and provides hands-on experience in melon seedling cultivation.Results: Participants’ enthusiasm and confidence in applying the seeding techniques learned reflect the effectiveness and practicality of the training methods in supporting home-based melon cultivation. This work is hoped to empowers women in managing home gardens, contributing to both economic resilience and household food security.